Technique for secondary modification after maxillary resection and reconstruction for soft tissue flap fixation before prosthesis addition: a case report - Atsushi Abe; Kenichi Kurita; Hiroki Hayashi; Yu Ito (BMC, 2019)
Abstract Background The removal of maxillary carcinoma causes various types of tissue defects, which can be corrected by free flap reconstruction. In flap reconstruction after maxillary cancer resection, ensuring prosthesis stability is frequently difficult owing to the flap's weight. Therefore, a second modification technique is required for improvement of configuration. This case where flap suspension and flap modifying surgery were performed using anchor system for the extensive complete maxillectomy case. Case presentation The patient was a 56-year-old male, who underwent an extensive total maxillectomy and flap reconstruction using the rectus abdominus muscles in May 2005. Postoperatively, due to the difficulties of wearing a maxillary denture, he was transferred to our department with the chief complaint of morphological improvement. The maxillary bone had already been removed from the midline with the rectus abdominus muscle flap sutured directly to the soft palate without oral vestibule, and the flap margin was moving together with the surrounding soft tissue. The flap size was 70 × 50 mm, which was sagging due to its own weight and was in contact with mandibular molars, reducing the volume of the oral cavity without a denture being worn. Flap reduction and lifting the flap were performed under general anesthesia using 3 Mitek anchors implanted in the zygomatic bone, and the anchor suture was placed through the subcutaneous tissue to lift the flap. Postoperatively, the prosthesis was stable. No recurrence of flap sagging or wound infection was seen 3 years after surgery. Conclusions The second modification technique after maxillary cancer resection is useful for ensuring prosthesis stability. This method can be used before prosthesis addition. We could obtain remarkable denture stability by flap suspension using anchor system and a flap-modifying operation for the patient who had undergone maxilloecotomy. The denture was stabilized by using anchors for the elevated flap and flap loss technique and by performing vestibuloplasty for support.